Malnutrition Amongst HIV Adult Patients in Selected Hospitals of Bushenyi District in Southwestern Uganda. - Odwee, Ambrose; Keneth Iceland, Kasozi; Acup, Christine Amongi; Kyamanywa, Patrick; Ssebuufu, Robinson; Obura, Richard; Agaba, Jude B.; Makeri, Danladi; Kirimuhuzya, Claude; Sasirabo, Olivia; Bamaiyi, Pwaveno H. (Kabale University, 2023)
Background: Malnutrition is an important clinical outcome amongst HIV patients in developing countries and in Uganda, there is scarcity of information on its prevalence and risk factors amongst HIV adult patients. Methods: A cross-sectional study amongst 253 HIV patients in Bushenyi district assessed their nutritional status using the body mass index (BMI) and mid-upper arm circumference (MUAC), and a questionnaire was used to identify major risk factors. Results: The mean age of the study participants was 38.74 ± 0.80 yrs, while females and males were 52.2% and 47.8% respectively. Prevalence of malnutrition was 10.28% (95% CI: 6.82 – 14.69) in the study. Major socio-economic factors associated with malnutrition were being female, unemployed, dependent and with many family members. Patients with opportunistic infections, low adherence to HAART, and stage of HIV/AIDS had a higher risk of malnutrition Discussion: In rural communities, a majority of malnourished patients are elderly and these were identified as priority groups for HIV outreach campaigns. The current policy of prioritizing children and women is outdated due to changing disease dynamics, thus showing a need to revise extension service provision in rural communities. Conclusions: Malnutrition is a threat in HIV adult patients in rural communities of Uganda. Keywords: Malnutrition, HIV Adult PPatients, Bushenyi District,Uganda.